The Use of JKN Mobile Application in Improving Patient Satisfaction in Registration Services at Kauman Baru Health Center, Ponorogo Regency - Aisah Nur Rahmawati; Rumpiati Rumpiati (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
Digital transformation in healthcare services encourages technology-based innovations, one of which is the Mobile JKN application. This application is expected to improve service efficiency and patient satisfaction, especially in the registration process at healthcare facilities. However, the extent to which this application positively impacts patient satisfaction still needs further investigation. This study aims to determine the relationship between the use of the Mobile JKN application and patient satisfaction, as well as to identify influencing factors and usage barriers at Puskesmas Kauman Baru, Ponorogo Regency. This research is a descriptive quantitative study involving 50 respondents selected using purposive sampling. Data collection was conducted through questionnaires, observation, and interviews. Data were analyzed descriptively and using Spearman correlation tests with the assistance of SPSS software. The results showed a significant relationship between the use of Mobile JKN and patient satisfaction (ρ = 0.318; p = 0.025). The use of the Mobile JKN application contributed positively to satisfaction, mainly due to ease of access, time efficiency, and the majority of respondents being in the productive age range (20-40 years). The main barriers in using the Mobile JKN application included difficulties faced by the elderly, technical issues, and limited network access. Education and technical support are needed to ensure more optimal implementation across all age groups.